Taxonomic and functional differentiation of freshwater fish communities in Western Indian Ocean islands: implications for eDNA-based biomonitoring - Jannel LA; Jourand P; Chabanet P; Valade P (Aquatic Ecology, 2026)

Transition from spot to long-lived eruptive activity in continental rifting tracked by monitoring soil degassing - O. Munguiko Munyamahoro; G. Boudoire; E. Regis; S. Valade; D. Ciza; D. Coppola; R. Campion; P.-J. Gauthier; S. Maska; P. Mataba; G. Mavonga Tuluka; A. Tumaini Sadiki; et al. (Journal of Volcanology and Geothermal Research, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Shallow magma convection evidenced by excess degassing and thermal radiation during the dome-forming Sabancaya eruption (2012–2020) - D. Coppola; S. Valade; P. Masias; M. Laiolo; F. Massimetti; A. Campus; R. Aguilar; R. Anccasi; F. Apaza; B. Ccallata; C. Cigolini; L. F. Cruz; et al. (Bulletin of Volcanology, 2022)
We used a large set of satellite- (visible, infrared, and radar images from Planetscope, MODIS, VIIRS, Sentinel2, Landsat 8, and Sentinel 1) and ground-based data (optical images, SO 2 flux, shallow seismicity) to describe and characterize the activity of the Sabancaya volcano during the unrest and eruption phases that occurred between 2012 and 2020. The unrest phase (2012–2016) was characterized by increasing gas and thermal flux, sourced by a convective magma column rising along with the remnants of a buried plug still permeable to fluid flow. Conversely, a new conduit, adjacent to the previous one, fed the eruptive phase (2016–2020) which was instead characterized by a discontinuous extrusive activity, with phases of dome growth (at rates from 0.04 to 0.75 m 3 s −1 ) and collapse. The extrusive activity was accompanied by fluctuating thermal anomalies (0.5–25 MW), by irregular SO 2 degassing (700–7000 tons day −1 ), and by variable explosive activity (4–100 events d −1 ) producing repeated vulcanian ash plumes (500–5000 m above the crater). Magma budget calculation during the eruptive phase indicates a large excess of degassing, with the volume of degassed magma (0.25–1.28 km 3 ) much higher than the volume of erupted magma (< 0.01 km 3 ). Similarly, the thermal energy radiated by the eruption was much higher than that sourced by the dome itself, an unbalance that, by analogy with the degassing, we define as “excess thermal radiation”. Both of these unbalances are consistent with the presence of shallow magma convection that fed the extrusive and explosive activity of the Sabancaya dome.

Upstream migration of amphidromous gobies of La Réunion Island: implication for management - R. Lagarde; N. Teichert; G. Boussarie; H. Grondin; P. Valade (Fisheries Management and Ecology, 2015)
Diadromous species of tropical islands face numerous anthropogenic disturbances. Understanding how these disturbances affect the population dynamic of these species is important to develop ecologically based management measures. The upstream migration dynamics of two amphidromous gobies, Sicyopterus lagocephalus (Pallas) and Cotylopus acutipinnis (Guichenot), was described using intensive fishway monitoring (28 sampling dates over 1.5 years, 13 000 S. lagocephalus , 23 000 C. acutipinnis captured). Migration peak occurred for both species during the afternoon at the end of austral winter/beginning of austral summer. Abundance and size of fish caught in the river showed a marked impact of a dam (six sampling dates approximately 4000 individuals of each species captured). This study provides critical data for better management of fishways used by tropical amphidromous gobies. It appears especially important to reduce unwanted rheotactic sources that attract the fish away from the fishway's entrance.

Breeding pattern and nest guarding in Sicyopterus lagocephalus, a widespread amphidromous Gobiidae - N. Teichert; P. Keith; P. Valade; M. Richarson; M. Metzger; P. Gaudin (Journal of Ethology, 2013)

Development of a key using morphological characters to distinguish south‐western Indian Ocean anguillid glass eels - É. Réveillac; P.‐A. Gagnaire; R. Lecomte‐Finiger; P. Berrebi; T. Robinet; P. Valade; É. Feunteun (Journal of Fish Biology, 2009)
Two morphological characters were examined in 4099 anguillid glass eels sampled in four south‐western Indian Ocean islands, and resulting identifications were tested using genetic analysis. Distance between the origin of the dorsal and anal fins as related to total length and tail and caudal fin pigmentation enabled formulation of a useful field identification key, which was able to discriminate 4036 glass eels of the regional species Anguilla bicolor bicolor , Anguilla marmorata and Anguilla mossambica , and excluded the occurrence of Anguilla nebulosa labiata in the sample.

Clues to the location of the spawning area and larval migration characteristics of Anguilla mossambica as inferred from otolith microstructural analyses - É. Réveillac; T. Robinet; M.‐W. Rabenevanana; P. Valade; É. Feunteun (Journal of Fish Biology, 2009)
The spawning area location and the larval migration characteristics of Anguilla mossambica were studied through the examination of early life‐history traits (ELHT) inferred from otolith microstructural analyses of 122 glass A. mossambica collected along the eastern coast of Madagascar, in the south‐western Indian Ocean. Backcalculated hatching dates of leptocephali that recruited between November 2005 and February 2006 suggested that spawning was continuous from June to November 2005, although individual migration duration periods were variable. Larvae that exhibited the highest daily otolith growth rates had the shortest leptocephalus durations and total length ( L T ) at recruitment, possibly because they reached the competence to metamorphose more rapidly and to recruit to fresh waters. Migration durations and L T increased from north to south on the Malagasy eastern coast, supporting earlier suggestions that A. mossambica spawns north‐east of Madagascar, west of the Mascarene Ridge in the Indian Ocean.

New clues for freshwater eels (Anguilla spp.) migration routes to eastern Madagascar and surrounding islands - T. Robinet; E. Réveillac; M. Kuroki; J. Aoyama; K. Tsukamoto; M. W. Rabenevanana; P. Valade; P.-A. Gagnaire; P. Berrebi; E. Feunteun (Marine Biology, 2008)

RFLP and semi‐multiplex PCR‐based identification of four eel species from the south‐western Indian Ocean region - P. A. Gagnaire; K. Tsukamoto; J. Aoyama; Y. Minegishi; P. Valade; P. Berrebi (Journal of Fish Biology, 2007)
To make the assignment of elvers to species more easily attainable and reliable, unpublished and recently published mitochondrial DNA sequences were used to design molecular determination approaches not based on sequencing. Two methods were proposed based on 16SrRNA single nucleotide polymorphism analysis, which improve identification of the four eel species living in the south‐western Indian Ocean region.